Halal Logistics Certificate in Malaysia: Challenges and Practices - Nuur Fathin Roslan; Fauziah Abdul Rahman; Faradina Ahmad; Noor Irdiana Ngadiman Ngadiman (International Journal of Supply Chain Management, 2016)
This paper illustrate challenges and practices of Halal logistics certificate in Malaysia. The concept of Halalan Toyyiban has been introduced, where the concept starts from the farm until consumption. This means all the raw materials, material handling, storage, warehousing, and transportation should use the halal concept across the supply chain. Under this concept logistics activity involved in term of how the goods transferred from one places to other place, storage place to keeps the goods , material handling and other logistics activities. Halal Logistics is created by Halal logistics Service Provider (LSP) to meet the demand from halal manufacturer in order to maintain the integrity for halal products. There was only one LSP company that introduced this new concept in their operation, there is about nine companies certified with Halal Logistics Certificate. The objective of this research is to explore the LSP Companies that have Halal Logistics Certificate from the authority, to determine the challenges faced by them to adopt Halal Logistics in their operation and to provide guideline for other LSP Companies those interested to apply for Halal Logistics Certificate in the next around .